Constitutional rights expansion and contributions from Robert Alexy’s theory / A expansão dos direitos fundamentais e a contribuição teórica de Robert Alexy - Morais, Fausto Santos de; Zolet, Lucas (Revista Brasileira de Direito, 2016)
Abstract: This paper, developed through the phenomenological-hermeneutical method, aims to research the Principle of Proportionality resulting from the Expansion hypothesis of Fundamental Rights. Based on this premise, it will present the contributions of the employment of Proportionality, considering the theoretical perspective of Robert Alexy. The relevance of this work, therefore, is founded especially on the assumption that the Expansion of Fundamental Rights and Robert Alexy’s theory can contribute to this matter.Keywords: Robert Alexy; Constitutional Rights; Proportionality.  Resumo: Este trabalho, produzido mediante o método fenomenológico-hermenêutico, propõe o estudo da Inflação dos Direitos Fundamentais decorrente do uso do Princípio da Proporcionalidade. Com base nessa premissa, apresentar-se-á as contribuições do emprego da Proporcionalidade considerando a influência teórica de Robert Alexy. A relevância deste trabalho, portanto, funda-se especialmente no pressuposto que a Inflação dos Direitos Fundamentais e como a teoria de Robert Alexy pode contribuir a essa discussão.Palavras-chave: Robert Alexy; Direitos Fundamentais; Proporcionalidade.